Kepemimpinan Transformasional, Motivasi, Dan Disiplin Kerja: Analisis Faktor Penentu Kinerja Karyawan PT. Matahari Department Store Balikpapan - Jun Prasetyo, Ridho; Tanan, Keliyanti; Rizky Kautsar Lauw, Pratama; Norhidayati, Norhidayati; Handayani, Lilik (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Balikpapan, 2025)
This research investigates the impact of transformational leadership, work motivation, and work discipline on the performance of employees at PT Matahari Department Store, Division III, Balikpapan Superblock (BSB). The study population consisted of 66 employees, from which a sample of 60 respondents was selected via purposive sampling. Utilizing performance appraisal data from 2020-2024 and multiple linear regression analysis, the study sought to understand these relationships. The findings reveal a coefficient of determination (R2) of 0.657, indicating that 65.7% of the variance in employee performance can be explained by the three independent variables combined. Partial test results show that transformational leadership (t-value 2.210) and work discipline (t-value 3.937) each have a statistically significant positive effect on performance. Conversely, work motivation (t-value 1.642) did not demonstrate a significant partial effect on performance. However, when assessed simultaneously, transformational leadership, work motivation, and work discipline collectively exert a significant influence on employee performance, with a calculated F-value of 35.800 far exceeding the F-table value of 2.769.